2020
DOI: 10.1155/2020/4235909
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Undergo Functional Reprogramming to Generate Immunosuppression through HIF-1α Signaling Pathway in the Late Phase of Sepsis

Abstract: Severe pneumonia with sepsis is characterized by a dysregulated inflammatory response of endotoxin. In our study, we attempted to investigate the roles of the immune guardian cells (monocytes) in the immune-inflammatory response of severe pneumonia-induced sepsis. We performed analysis in the blood samples of human and animals with ELISA, western blot, flow cytometry (FCM) methods, etc. Results showed that the proinflammatory status shifted to hypoinflammatory phases during the sepsis process. In a clinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Hypoxia facilitates malignant tumor escape from immune surveillance 15–17 . Hypoxia decreases natural killer (NK) and T cell survival and weakens the immune function of dendritic cells (DCs) through a mechanism involving hypoxia‐inducible factor‐1 (HIF‐1) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia facilitates malignant tumor escape from immune surveillance 15–17 . Hypoxia decreases natural killer (NK) and T cell survival and weakens the immune function of dendritic cells (DCs) through a mechanism involving hypoxia‐inducible factor‐1 (HIF‐1) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…It is lately documented that HDAC4 elevation causes H9C2 cell death and mitochondrial dysfunction in hypoxia/reoxygenation injury [ 15 ]. Hypoxia-inducing factor 1 (HIF-1) signaling pathway is the channel that monocytes undergo reprogramming to generate immunosuppression in the late stage of sepsis [ 16 ]. It has been proved that downregulating the activated HIF-1α, the HDAC4 client transcription factor, could improve the prognosis of sepsis [ 17 ] and relieve myocardial injury during sepsis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our bioinformatics analyses (Fig. S5 ) and literature [ 28 ] showed that both miR-150-5p and miR-21-5p modulated HIF-1 cellular signaling pathway, whilst the HIF-1α signaling pathway was shown to be attributable to the immunosuppression through the immune cell (e.g., monocytes) phenotype changes reprogramming in the late stage of sepsis.…”
Section: Discussionmentioning
confidence: 73%